Novel associations of CPS1, MUT, NOX4, and DPEP1 with plasma homocysteine in a healthy population: a genome-wide evaluation of 13 974 participants in the Women's Genome Health Study. - Paré, G; Chasman, D; Parker, A; Zee, R; Mälarstig, A; Seedorf, U; Collins, R; Watkins, H; Hamsten, A; Miletich, J; Ridker, P (2009)
BACKGROUND: Homocysteine is a sulfur amino acid whose plasma concentration has been associated with the risk of cardiovascular diseases, neural tube defects, and loss of cognitive function in epidemiological studies. Although genetic variants of MTHFR and CBS are known to influence homocysteine concentration, common genetic determinants of homocysteine remain largely unknown. METHODS AND RESULTS: To address this issue comprehensively, we performed a genome-wide association analysis, testing 336 469 single-nucleotide polymorphisms in 13 974 healthy white women. Although we confirm association with MTHFR (1p36.22; rs1801133; P=8.1 x 10(-35)) and CBS (21q22.3; rs6586282; P=3.2 x 10(-10)), we found novel associations with CPS1 (2q34; rs7422339; P=1.9 x 10(-11)), MUT (6p12.3; rs4267943; P=2.0 x 10(-9)), NOX4 (11q14.3; rs11018628; P=9.6 x 10(-12)), and DPEP1 (16q24.3; rs1126464; P=1.2 x 10(-12)). The associations at MTHFR, DPEP1, and CBS were replicated in an independent sample from the PROCARDIS study, whereas the association at CPS1 was only replicated among the women. CONCLUSIONS: These associations offer new insight into the biochemical pathways involved in homocysteine metabolism and provide opportunities to better delineate the role of homocysteine in health and disease.